The role of YRNA-derived small RNAs in atherosclerosis development and progression – modeled and analyzed using Petri nets - Trzebiatowski, Adam; Rybarczyk, Agnieszka (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Non-coding RNAs regulate diverse aspects of development, homeostasis, and disease. Among them, YRNA–derived small RNAs (s-RNYs) have attracted clinical interest as potential biomarkers due to their high abundance across human tissues, body fluids, and tumors. Despite major advances in understanding atherogenesis, the overall picture remains incomplete, limiting therapeutic progress. To address this gap, we built a systems model of atherogenesis using classical Petri nets, integrating recent insights of s-RNY functions in monocytes and macrophages alongside oxidative stress, inflammatory signaling, and key atherogenic pathways. Using t-invariant analysis, in silico knockouts, and dynamic simulations, we found that dual-target strategies, such as suppression of oxidative stress combined with inhibition of either (1) toll-like receptor 7 (TLR7), (2) s-RNYs, or (3) the pro-inflammatory cytokine interleukin-6 (IL-6), attenuate lesion progression. These findings support multipathway combination therapy as a promising direction to more effective treatment of atherosclerosis.